Adenosine A(2B) receptor-mediated leukemia inhibitory factor release from astrocytes protects cortical neurons against excitotoxicity - Moidunny, Shamsudheen (BioMed Central, 2012)
BACKGROUND: Neuroprotective and neurotrophic properties of leukemia inhibitory factor (LIF) have been widely reported. In the central nervous system (CNS), astrocytes are the major source for LIF, expression of which is enhanced following disturbances leading to neuronal damage. How astrocytic LIF expression is regulated, however, has remained an unanswered question. Since neuronal stress is associated with production of extracellular adenosine, we investigated whether LIF expression in astrocytes was mediated through adenosine receptor signaling. METHODS: Mouse cortical neuronal and astrocyte cultures from wild-type and adenosine A(2B) receptor knock-out animals, as well as adenosine receptor agonists/antagonists and various enzymatic inhibitors, were used to study LIF expression and release in astrocytes. When needed, a one-way analysis of variance (ANOVA) followed by Bonferroni post-hoc test was used for statistical analysis. RESULTS: We show here that glutamate-stressed cortical neurons induce LIF expression through activation of adenosine A(2B) receptor subtype in cultured astrocytes and require signaling of protein kinase C (PKC), mitogen-activated protein kinases (MAPKs: p38 and ERK1/2), and the nuclear transcription factor (NF)-κB. Moreover, LIF concentration in the supernatant in response to 5′-N-ethylcarboxamide (NECA) stimulation was directly correlated to de novo protein synthesis, suggesting that LIF release did not occur through a regulated release pathway. Immunocytochemistry experiments show that LIF-containing vesicles co-localize with clathrin and Rab11, but not with pHogrin, Chromogranin (Cg)A and CgB, suggesting that LIF might be secreted through recycling endosomes. We further show that pre-treatment with supernatants from NECA-treated astrocytes increased survival of cultured cortical neurons against glutamate, which was absent when the supernatants were pre-treated with an anti-LIF neutralizing antibody. CONCLUSIONS: Adenosine from glutamate-stressed neurons induces rapid LIF release in astrocytes. This rapid release of LIF promotes the survival of cortical neurons against excitotoxicity.